Clofibrate Increases Long-Chain Fatty Acid Oxidation by Neonatal Pigs. Issue 11 (3rd September 2014) - Bai, Xiumei; Lin, Xi; Drayton, Josephine; Liu, Yulan; Ji, Cheng; Odle, Jack
Abstract: Background: Utilization of energy-dense lipid fuels is critical to the rapid development and growth of neonates. Objective: To increase efficiency of milk fat utilization by newborn pigs, the effect of clofibrate on in vivo and in vitro long-chain fatty acid (LCFA) oxidation was evaluated. Methods: Newborn male pigs were administered 5 mL of vehicle (2% Tween 80) with or without clofibrate (75 mg/kg body weight) once daily via i.g. gavage for 4 d. Total LCFA oxidative capacity was measured in respiration chambers after gastric infusion ( n = 5 per treatment) with isoenergetic amounts of [1- 14 C]triglycerides (TGs), either oleic acid (18:1n–9) TG [3.02 mmol/kg body weight (BW) 0.75 ] or erucic acid (22:1n–9) TG (2.46 mmol/kg BW 0.75 ). Total expired 14 CO2 was collected and quantified at 20-min intervals over 24 h. Hepatic in vitro LCFA oxidation was determined simultaneously using [1- 14 C]oleic acid and erucic acid substrates. Results: The in vivo 24-h accumulative [1- 14 C]TG oxidation (percentage of energy intake/kg BW 0.75 ) tended to increase with clofibrate supplementation ( P = 0.10), although there was no difference in the peak or mean utilization rate. The maximal extent of oleic acid TG oxidation was 1.6-fold that of erucic acid TG ( P < 0.006). Hepatic in vitro LCFA oxidation increased 61% with clofibrate ( P < 0.0008). The increase in mitochondria was 4-fold greater than in peroxisomes. The relative abundance of mRNA increased 2- to 3-fold for hepatic peroxisome proliferator-activated receptor α and its target genes (fatty acyl-coenzyme A oxidase and carnitine palmitoyltransferase) in the pigs that were administered clofibrate ( P < 0.04). Conclusion: Clofibrate may improve in vivo LCFA oxidative utilization in neonatal pigs.